Interaction of Judgemental and Statistical Forecasting Methods: Issues & Analysis - Bunn, Derek; Wright, George (Management Science, 1991)
This paper reviews several of the current controversies in the relative value of judgemental and statistical forecasting methods. Where expert, informed judgemental forecasts are being used, a critical analysis of the evidence suggests that their quality is higher than many researchers have previously asserted, and circumstances favourable to this are identified. The issue of the interaction of judgemental and statistical methods is, however, identified as a more worthwhile line of inquiry, and research in this area is reviewed, differentiating approaches aimed at synthesising both of these inputs.